2016
DOI: 10.1093/europace/euw346
|View full text |Cite
|
Sign up to set email alerts
|

Human ventricular activation sequence and the simulation of the electrocardiographic QRS complex and its variability in healthy and intraventricular block conditions

Abstract: AimsTo investigate how variability in activation sequence and passive conduction properties translates into clinical variability in QRS biomarkers, and gain novel physiological knowledge on the information contained in the human QRS complex.Methods and resultsMultiscale bidomain simulations using a detailed heart-torso human anatomical model are performed to investigate the impact of activation sequence characteristics on clinical QRS biomarkers. Activation sequences are built and validated against experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 20 publications
3
59
0
Order By: Relevance
“…Specifically, the APD 90 was mainly used for the measurement of the APDs, which was measured as the time interval between the 90% of the voltage at the upstroke and at the down stroke of the APs. The tissue activation was mainly in accordance with the human ventricular activation sequence of Cardone-Noott et al [4], which the left ventricle (LV) endocardial surface was activated within 30ms and the transmural propagation accomplished in 35ms. As illustrated in the Tables 1-3, the model parameter values were modified to accommodate post-infarction condition for epicardial, endocardial and midmyocardial myocytes.…”
Section: Electrophysiology and Tissue Modelsupporting
confidence: 58%
“…Specifically, the APD 90 was mainly used for the measurement of the APDs, which was measured as the time interval between the 90% of the voltage at the upstroke and at the down stroke of the APs. The tissue activation was mainly in accordance with the human ventricular activation sequence of Cardone-Noott et al [4], which the left ventricle (LV) endocardial surface was activated within 30ms and the transmural propagation accomplished in 35ms. As illustrated in the Tables 1-3, the model parameter values were modified to accommodate post-infarction condition for epicardial, endocardial and midmyocardial myocytes.…”
Section: Electrophysiology and Tissue Modelsupporting
confidence: 58%
“…Another work by Cardone-Noott et al [13] investigated the effect of changes in conductivities on the ECG morphology and how the variability in the activation sequence relates to changes in QRS biomarkers, by designing a 3D simulation pipeline with a human volumetric mesh and activation model based on the cellular O'Hara-Rudy model. Phenomenological approaches to modelling and simulation of electrical propagation have also been proposed using fast algorithms based on graph based theory [95,96].…”
Section: Ecg Computer Simulationsmentioning
confidence: 99%
“…Vigmond et al [100] for example showed the importance of superior vena cava and pulmonary vein openings in rotors by using a model of the atria built with two spheres containing holes as anatomical elements. However, despite being very useful because of their simplicity, Computational pipeline for ECG simulation from magnetic resonance images through 3D meshes and cellular electrophysiological models (left, from Zacur et al [87]) and the obtained simulation of the cardiac electrical activity (right, from Cardone-Noott et al [13]). Personalized cardiac magnetic resonance images (1) are segmented and preprocessed (2).…”
Section: Ecg Computer Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since their invention, ECGs are still the most widely used non-invasive method to assess cardiac function and to investigate cardiac disorders (25). Despite the known natural variability to ventricular activation sequences across a healthy population, which translates to a variability observed in the QRS complexes of human ECGs, certain sites of early activation within the left and right ventricles have been identi ed in the literature, which de ne normal electrical excitation patterns (25). Thus, when interested in building an accurate multiscale cardiac model that accounts for electrophysiology within anatomically accurate cardiac domains, it becomes necessary to ensure that the resulting ECGs from the model match those clinical, both in health and in disease.…”
Section: Introductionmentioning
confidence: 99%